2017
DOI: 10.1002/macp.201700313
|View full text |Cite
|
Sign up to set email alerts
|

Successful UV‐Induced RICFP of Epoxy‐Composites

Abstract: The UV‐curing of epoxy monomers by cationic photopolymerization is a powerful method for the production of polymer materials. The limit of film thickness in cationic photopolymerization of epoxy monomers has been recently overcome by introducing a novel radical induced cationic frontal polymerization (RICFP) system within this research group. The possibility to cure epoxides in bulk by UV‐light promoted here presents the novel approach to photocured composites. In the present work, the recently established RIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…It was demonstrated in previous reportes that FP is started by the dissociation of a radical thermal initiator promoted by the heat released during surface UV‐initiated cationic ring‐opening polymerization. Subsequently, the carbon‐centred radicals are oxidized to carbocations by the presence of the iodonium salt through a radical‐induced cationic mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated in previous reportes that FP is started by the dissociation of a radical thermal initiator promoted by the heat released during surface UV‐initiated cationic ring‐opening polymerization. Subsequently, the carbon‐centred radicals are oxidized to carbocations by the presence of the iodonium salt through a radical‐induced cationic mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Crivello also reported radical‐induced cationic FP (RICFP) to realize UV crosslinking through the thickness of a photocurable formulation. In a more recent paper, we reported the possibility of curing bulk pristine epoxy formulations containing SiO 2 by RICFP; the influence of the filler content on frontal propagation was investigated, showing a decrease of front velocity and front starting time with increasing filler content . We have also reported the UV‐crosslinking preparation of epoxy–glass fibre composites via RICFP.…”
Section: Introductionmentioning
confidence: 99%
“…The frontal velocity decreased from 9 cm/min to 2.8 cm/min with increasing zirconia content from 0 to 80 phr [ 40 ]. Using the same formulation of BADGE and photo and thermal radical initiator, Klikovits et al [ 131 ], studied the effect of silica nanoparticles on frontal polymerization and mechanical properties of a BADGE-silica nanocomposite. Their studies showed that silica concentration of up to 3 phr can give a reproducible front, whereas 4 and 5 phr required a high-UV-intensity floodlight due to limited light penetration, in order to propagate the front.…”
Section: Effect Of Fillers In Epoxy Compositesmentioning
confidence: 99%
“…UV-cured bulk epoxy composites were successfully produced by Radical Induced Cationic Frontal Polymerization (RICFP); it was shown that the FP is started by the dissociation of a radical, thermal initiator (RTI) promoted by the heat released during surface UV-induced cationic ringopening polymerization. Subsequently, the carboncentered radicals are oxidized to carbocations by the presence of the iodonium salt in a RICP mechanism [3].…”
Section: Introductionmentioning
confidence: 99%